Jazzercise as a training mode in women - Martin, Sue (My University, 1985)
Twenty-one female Ss participated in either a 2-day (n=5) or a 3-day (n=16) Jazzercise program for 7 wks to determine if Jazzercise training would elicit changes in maxVO2 and body composition. The Ss ranged in age from 18 ? 33 yrs. All Ss were given pre (T1) and post (T2) maxVO2 tests using the Modified Astrand Protocol and were hydrostatically weighed. A target HR of 75% of age-predicted MHR was assigned and the THRs were recorded. The 2 and 3 day groups worked at an average intensity of 78.8% and 77.3%, respectively. A mixed design 2 way ANOVA was used to analyze the following variables: body weight, % body fat, R, maxV02 (1*min-1 and ml*kg*min-1), treadmill run time, maxVE, and MHR. Sig (p < .05) increases were found for both groups for maxV02, both relative and absolute. Sig (p < .05) decreases were found for both groups for % body fat. There were no sig (p .05) changes for either group for all other variables with the exception of a sig (p < .05) increase in ventilatory efficiency for the 3-day group. There were no sig (p > .05) interactions between groups for all variables with the exception of ventilatory efficiency. It was concluded that participation in Jazzercise either 2 or 3 times per wk is effective for producing positive body composition and cardiovascular responses.
Keywords: Jazzercise -- Physiological aspects